Metropolitanising small European stateless city-regionalised nations - Calzada, I (Routledge, 2018)
This article introduces three small, European stateless nations that – invigorated by pervasive metropolitanisation phenomena – are increasingly shaping calls for devolution: Catalonia, the Basque Country and Scotland. These three nations are re-scaling their respective nation-states (Spain and the UK) in different ways: (i) being bolstered by their metropolitan hubs (Barcelona, Bilbao, and Glasgow) and (ii) generating a stateless ‘civic nationalism’ rooted in the metropolitan ‘right to decide’. Oppositional response to this ‘civic nationalism’ has re-emerged as state-centric ‘ethnic nationalism’. This article concludes that gaining or lacking metropolitan support for the ‘right to decide’ will establish the future directions of devolution debates.